DFT calculations of the synergistic effect of λ-MnO2/graphene composites for electrochemical adsorption of lithium ions. Issue 15 (1st April 2019) - Zhang, Huixin; Du, Xiao; Ding, Shengqi; Wang, Qiang; Chang, Lutong; Ma, Xuli; Hao, Xiaogang; Pen, Changjun
Abstract : Density functional theory (DFT) was used to calculate the geometric and electronic structure of λ-MnO2 and λ-MnO2 /graphene composites. Abstract : Recently, the composite of spinel-type manganese oxide (λ-MnO2 )/graphene has drawn wide attention because of its good electrochemical adsorption selectivity for low concentrations of Li + ions from lake brine or seawater to cope with the fast-rising demand of lithium resources. In this composite, the synergistic effect between the good selectivity of λ-MnO2 for Li + ions and the excellent conductivity of graphene play an important role for the electrochemical adsorption of Li + ions. In order to reveal the synergistic mechanism in the electronic conductivity, the ionic conductivity and the ion selectivity of the λ-MnO2 /graphene composite, density functional theory (DFT) calculations combined with electrochemical adsorption experiments were carried out. The calculation results show that the enhanced electronic conductivity of the composite is due to the decrease of the band gap ( E g ) in the λ-MnO2 /graphene composite compared with pure λ-MnO2 . Meanwhile, the graphene composited with λ-MnO2 decreased the diffusion energy barrier of Li + ions in λ-MnO2 . In addition, the competitive adsorption of Li +, Na + and Mg 2+ ions were investigated by the nudged elastic band (NEB) method and charge distribution analysis. The results show that Li + ions in λ-MnO2 exist in their pure ion state and have the lowest diffusion energy barrier compared with Na + and Mg 2+ . The results of the DFT calculations were validated by cyclic voltammetry, electrochemical impedance spectroscopy and electrochemical adsorption experiments.